Mathematics Learning with The Teams Games Tournament (TGT) Model for Students at MAN 1 Banyumas - Tri Handoko, Bangkit (International Proceedings of Nusantara Raya, 2022)
Student competence is measured based on certain indicators. One of the advantages that can be obtained from the implementation of the Computer-Based National Assessment (ANBK). About these aspects, identification of learning difficulties based on the results of ANBK needs to be carried out to improve the learning process on aspects of teaching methods, assessment methods, decisions on learning implementation, and assessment of learning implementation in schools. Several studies have shown that mathematics is widely experienced by students at various levels of education as a difficult subject. Awareness of the difficulties that students experience in their learning process is an important first step for teachers to design and manage mathematics lessons. This research uses a qualitative method with a descriptive approach. The process of collecting research data through observation, interviews, and documentation. The teacher performs various actions based on his findings in diagnosing students' difficulties in learning mathematics. The main activity performed by the teacher is to teach the Teams Games Tournament (TGT) method. The Team Games Tournament (TGT) applied at MAN 1 Banyumas is learning using academic tournaments, quizzes, and an individual progress score system, where each student competes as a representative of his team with other team members whose previous mathematics learning abilities are equivalent to theirs. Where the TGT applied at MAN 1 Banyumas encourages all students to have the same opportunity to represent their team in the assessment.